Estimation of critical properties of typically Colombian vacuum residue SARA fractions - Yovani León, Adán; Parra, Martha; Grosso, Jorge Luis (CT&F - Ciencia, Tecnología y Futuro, 2008)
Knowledge of critical properties and the acentric factor is required in phase-equilibrium studies in different extraction processes conducted in the petroleum industry, particularly in the solvent deasphalting process. Correlations to estimate critical temperature, critical pressure and acentric factor values of SARA (Saturated, Aromatic, Resin, and Asphaltene) fractions of vacuum residue from the Barrancabermeja Refinery were determined from their physical properties such as density (molar volume) and molecular weight. New correlations for critical property prediction were evaluated using model molecules and the Avaullee and Satou's group contribution methods, respectively.